Munro Kerr's operative obstetrics - Arulkumaran, Sabaratnam; Robson, Michael (Saunders Elsevier, 2020)
This is a highly illustrated, practical book covering the obstetric and surgical procedures used in intrapartum care, including commonly used procedures and more rare techniques. The authors take a step-by-step approach to each technique and includes 'tips' and 'pointers', whilst contextualising this with the history of obstetric practice.